2020
DOI: 10.1021/acs.biomac.9b01753
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Shape-Memory Effect in Gelatin-Based Hydrogels

Abstract: Hydrophilic biopolymers display a strong tendency for self-organization into stable secondary, tertiary, and quaternary structures in aqueous environments. These structures are sensitive to changes in external conditions, such as temperature, pH or ions/salts, which may lead to molecular and/or macroscopic transitions. Here, we report on biopolymer-based stimuli-sensitive switchable matrices showing a shape-memory function as an output being alternatively switched by two different input signals, such as enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The networks are in the following referred to as G20_OEGy(z), with y = number average molar mass Mn of the OEG crosslinkers and z the thiol:methacrylate molar ratio. The gel content G, which is a measure of network formation, and the volumetric swelling Q of the G20_OEG1000(z) and G20_OEG3400(z) networks has been reported before [22] and is given in detail for the G20_OEG1500(z) in Supporting Information Table S1. As general trend, a reduction of G with increasing length of the crosslinker as well as with increasing z was observed, though there were only small differences between G20_OEGy(0.75) and G20_OEGy(1) samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The networks are in the following referred to as G20_OEGy(z), with y = number average molar mass Mn of the OEG crosslinkers and z the thiol:methacrylate molar ratio. The gel content G, which is a measure of network formation, and the volumetric swelling Q of the G20_OEG1000(z) and G20_OEG3400(z) networks has been reported before [22] and is given in detail for the G20_OEG1500(z) in Supporting Information Table S1. As general trend, a reduction of G with increasing length of the crosslinker as well as with increasing z was observed, though there were only small differences between G20_OEGy(0.75) and G20_OEGy(1) samples.…”
Section: Resultsmentioning
confidence: 99%
“…We recently introduced a gelatin-based covalent network system that is formed by reacting glycidylmethacrylated gelatin (GMA-gelatin) with oligo (ethylene glycol) (OEG)-,-dithiols (Figure 1A) [22]. The approach to crosslink gelatin by a bifunctional crosslinker has in the past been demonstrated to be beneficial for effectively establishing a polymer network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of gelatin significantly affected the hydrogel, and was responsible for the formation or deformation of a helical shape. Also, the study showed the potential activity of various chaotropic and kosmotropic salts which regulated the gelatin helicalization or conformational alterations [ 324 ].…”
Section: Applications In Tissue Engineering and Regenerative Medicmentioning
confidence: 99%
“…We recently introduced a gelatin-based covalent network system that is formed by reacting glycidyl methacrylated gelatin (GMA-gelatin) with oligo(ethylene glycol) (OEG) α,ω-dithiols ( Figure 1 A) [ 22 ]. The approach to crosslink gelatin by a bifunctional crosslinker has in the past been demonstrated to be beneficial for effectively establishing a poly-mer network.…”
Section: Introductionmentioning
confidence: 99%